Draft Genome Sequence of the Toxic Bloom-Forming Cyanobacterium Aphanizomenon flos-aquae NIES-81 - Cao, Huansheng (American Society for Microbiology, 2014)
Aphanizomenon flos-aquae is a toxic filamentous cyanobacterium that causes water blooms in freshwaters across the globe. We present the draft genome sequence of the A. flos-aquae strain NIES-81, which was determined by 454 pyrosequencing technology. The draft genome is ~5.7 Mb, containing 5,802 predicted protein-coding genes and 58 RNA genes, with a G+C content of 38.5%.